Atrial fibrillation, cognitive impairment, frailty and disability in older heart failure patients. Issue 8 (August 2016) - Pulignano, Giovanni; Del Sindaco, Donatella; Tinti, Maria D.; Di Lenarda, Andrea; Alunni, Gianfranco; Senni, Michele; Tarantini, Luigi; Cioffi, Giovanni; Barbati, Giulia; Minardi, Giovanni; Murrone, Adriano; Ciurluini, Paola; et al.
Abstract : Background: Aim of the study was to prospectively assess the relation between atrial fibrillation, cognitive impairment, frailty and disability in older patients with chronic heart failure . Methods: Three hundred thirty-one ambulatory community-living patients aged 70 years and older (mean 78 ± 6; range 70–93; 43% women) in stable conditions and optimized therapy were enrolled in seven heart failure cardiology clinics. Cognitive impairment was defined by a corrected Mini Mental State Examination scoreless than 24. Gait speed was used as marker of frailty and measured on a 4 m distance at usual pace. Results: Ninety-eight patients (30%) were on atrial fibrillation at enrolment and 20 (6%) had a history of paroxysmal/persistent atrial fibrillation. Patients with atrial fibrillation were more frequently women with severe valvular disease, preserved left ventricular ejection fraction and less frequently on beta-blockers. At multivariable analyses, atrial fibrillation emerged as independently related to cognitive impairment [odds ratio (OR) 1.909 (1.072–3.397); P  = 0.028], as well as to reduced gait speed [OR 4.366 (2.104–9.060); P  < 0.001]. Furthermore, atrial fibrillation was significantly associated with disability in either basic or instrumental activities of daily living. No differences were found in mortality and morbidity. Conclusion: Among patients with chronic heart failure, those with atrial fibrillation present a high prevalence of frailty, cognitive impairment and disability. The hypothetical mechanisms by which atrial fibrillation and heart failure may affect these conditions are multiple and further studies are warranted. However, screening for these variables in clinical practice is simple and inexpensive and may allow better strategies for intervention in this high-risk population.